COLONIAL SHADOWS AND LEGAL FORMALISM: A POSTCOLONIAL SOCIOLOGICAL CRITIQUE OF BUREAUCRACY IN INDONESIA - Raden Bima Adi; Reny Triwardani (Jurnal Analisa Sosiologi, 2025)
Indonesia’s independence in 1945 represented a definitive separation from colonial rule; however, its bureaucratic and legal institutions continue to mirror the vestiges of Dutch colonial governance. This paper conducts a critical examination of the enduring colonial logics that inform contemporary governance, law enforcement, and public administration. Employing a postcolonial sociological framework influenced by the works of Frantz Fanon and Syed Hussein Alatas, the study investigates historical continuities in administrative practices, hierarchical structures, and legal formalism. Through a qualitative content analysis of policy documents and legal texts, it demonstrates how state institutions perpetuate control, rigidity, and elitism, frequently alienating the public and undermining democratic ideals. Furthermore, the prioritisation of proceduralism over justice places marginalised groups at a disadvantage, thereby reinforcing structural inequities. This research posits that Indonesia’s independence remains predominantly symbolic unless these inherited colonial frameworks are actively deconstructed. It advocates for a decolonial transformation of governance that is congruent with the socio-cultural realities of the Indonesian populace. This article contributes to the development of postcolonial legal sociology by mapping the relationship between legal formalism and social exclusion in the context of Southeast Asian postcolonial states.